WEWENANG PELAKSANA TUGAS BUPATI KABUPATEN BOGOR DALAM PEMERINTAHAN BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014: Authority To Execute Duties Of Regent Of Bogor District In Government Based On Law Number 23 Of 2014 - Zahra Khairunisa; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2024)
Acting Officer is a temporary position specifically assigned to fill vacancies that occur with the aim of keeping the wheels of government running. The formulation of the problem in this article is whether the appointment of the acting Bogor Regency Regent is appropriate based on Law Number 23 of 2014 concerning Regional Government and how the authority of the acting Bogor Regency Regent in carrying out Regional Government duties based on Law Number 23 of 2014 concerning regional government. The research method used is normative, analyzed descriptively qualitative and drawing conclusions with deductive logic. The results of the research and discussion are the authority and duties of the PLT Regent of Bogor Regency are only based on general regulations, namely Article 65 paragraphs (1) and (2) concerning Regional Government which contains the Authority and Regional Head, not the PLT, and the authority of the PLT is limited by Article 132 A paragraph 1 of Law Number 49 of 2008. The conclusion is that there are no regulations that specifically regulate the Appointment of PLT Officials.